HUMANITIES IN HIGHER TECHNICAL EDUCATION: WAY TO THE FUTURE (Pedagogy of Higher and Secondary Education, 2008)
This article is devoted to the role of humanities in higher education, which positions itself as an integral process of upbringing, education and development hosed on acknowledgement ofperson’s ultimate value and provides student's mastering of practice-oriented knowledge, formation of personality capable of selfimplementation and self-development.
Keywords: cognition; development; dialog; educational techniques; fundamental education; higher technical education; humanities; humanization; pedagogical process; personality; scientific and technical knowledge; professional competence; studies